Tinjauan Yuridis Penggunaan Konten YouTube Sebagai Objek Jaminan Kredit di Bank - Siahaan, Josephine Clara Lamuli; Saidin, OK; Sukarja, Detania (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
This article aims to assess the compatibility between the regulations of Republic of Indonesia Government Regulation Number 24 of 2022 concerning the Creative Economy (PP Ekraf) and the practice of using YouTube content as collateral for credit in banks. The problem with this writing also focuses on the execution that can be implemented to use the content in a YouTube account as an object of fiduciary collateral. The legal research used in preparing this writing is normative legal research. The data was analyzed quantitatively, which was collected using library research techniques by interviewing to gather secondary data. This study concludes that YouTube content, as a form of copyrighted material, is considered a digital asset classified as an intangible movable object. This can be used as collateral for credit, subject to certain terms and conditions. In this case, if the debtor fails to fulfill their promise, the guarantee requires that execution be carried out. This can be done through either a public auction or a private sale, depending on the specific terms of the guarantee. If there is a dispute regarding the object of the credit guarantee, Article 40 of PP Ekraf states that the dispute can be resolved through both judicial and extrajudicial means.